PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Jesicca Ayu Rahmawati; Islamuddin Islamuddin (UM. Bengkulu, 2026)
This study aims to analyze the effect of work motivation and work discipline on employee performance at coffee shops in Bengkulu City. The research employed a quantitative method with a causal associative approach. The study population comprised operational employees at seven coffee shops in Bengkulu City, with a sample of 83 employees selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination (R²) with IBM SPSS Statistics version 26. The results indicate that work motivation has a positive and significant effect on employee performance (t = 6.892; sig. = 0.000). Work discipline also exerts a positive and significant effect on employee performance (t = 6.466; sig. = 0.000). Simultaneously, both variables significantly affect employee performance (F = 42.157; sig. = 0.000). The coefficient of determination (R²) of 0.513 indicates that both variables explain 51.3% of the variation in employee performance, while the remaining 48.7% is attributed to other variables outside the scope of this study. These findings imply that coffee shop management should concurrently strengthen work motivation and enforce work discipline to sustain optimal employee performance. Keywords: Work Motivation, Work Discipline, Employee Performance, Coffee Shop